Factors Affecting The Negative Difference Between Hospital Rates and INA-CBGS Rates for Ischemic Stroke Patients at dr. Soebandi General Hospital in Jember - Rachman Adji Prakoso; Abu Khoiri; Viera Wardhani3 (Jurnal Ners, 2026)
The National Health Insurance casemix-based payment system through INA-CBGs often causes discrepancies between actual costs and claim rates, particularly in cases of ischemic stroke, which are clinically complex. This study aims to analyze the factors that influence the negative difference between hospital rates and INA-CBGs rates for ischemic stroke patients at Dr. Soebandi General Hospital in Jember in 2024. The study employs a quantitative approach with a cross-sectional design and SEM-PLS analysis. A total of 81 JKN ischemic stroke patients were selected through stratified proportional sampling based on treatment class. The results showed that concordant comorbidity did not have a significant effect on severity (β = 0.159; p = 0.11), while discordant comorbidity had a positive and significant effect (β = 0.730; p < 0.001). Severity had a significant positive effect on LOS (β = 0.322; p < 0.001). In addition, LOS was found to have a significant negative effect on the rate difference (β = –0.724; p < 0.001). Meanwhile, the treatment class did not show a significant effect on the rate difference (β = 0.077; p = 0.29). The R² value of the rate difference was 0.508, indicating that the model was able to explain 50.8% of the variation in the rate difference. These findings confirm that the complexity of comorbidity and length of stay are the main determinants of hospital cost deficits.